Pre-Service EFL Teachers’ Noticing in Practicum Through Joint Reflection in the Turkish Context - Özkan Kırmızı; Aydan Irgatoğlu; Fatma Yasemin Bayındır Özkan (SAGE Open)
The present study was undertaken to analyze pre-service EFL teachers’ (PSTs) noticing during the practicum process over 14 weeks. In total, 26 PSTs took part in the present study. Data were collected through joint reflection sessions (JRSs). For JRS, PSTs met in their group every week after their practicum days and discussed what they noticed on that day. Basically, the study attempts to explore what salient or noteworthy classroom situation PSTs notice in their practicum as they are observing and whether they could the specifics of classroom situations and the broader principles of teaching and learning they represent. To problematize these, we used Pedagogical Content Knowledge framework. The results indicated that the PSTs mainly focused on communication, environment , and management categories . The study also showed that the PSTs mainly dealt with the order in the teaching process, with relatively superficial noticing regarding content.